Evaluating Supports for “All But Dissertation” Students - Beth Kania-Gosche; Yvonne Gibbs (Adult Education Research Conference, 2013)
The authors of this roundtable session will lead a discussion debating effective methods for evaluating support services for “All But Dissertation” students to better focus university resources.